Characteristics and properties of Co–Cr alloy coatings prepared by electrodeposition. (1st September 2020) - Mahdavi, Soheil; Allahkaram, Saeed Reza; Heidarzadeh, Akbar; Tavangar, Reza
ABSTRACT: Two different ways were used for preparing the electrodeposition baths. In the first bath, different concentrations of cobalt sulphate (up to 6 g L –1 ) and one complexing agent were employed. In the second bath, two different complexing agents and a constant concentration of cobalt sulphate were used. The results showed that the microstructure of the coatings was changed from amorphous to nano-crystalline by enhancing cobalt sulphate concentration in the bath No. 1. Current efficiency and thickness of the alloy coatings obtained from bath No. 2 were higher than those deposited from bath No. 1. However, reducing the bath temperature or raising the current density decreased the current efficiency, while increased Cr content and hardness of alloy coatings. The Co-29.3 wt-%Cr electrodeposit obtained from bath No. 2 at the optimum condition had better corrosion and wear resistance than Co-Cr and Cr films produced from bath 1, as well as the steel substrate.